PROBLEMS OF POPULARIZING VOCATIONAL EDUCATION AMONG YOUNG PEOPLE (Innovative professional education, 2025)
The main problems of popularisation of vocational education in Ukraine are analysed. The main options for overcoming these obstacles to the development of vocational education are considered
Keywords: vocational education, gender imbalance, labour market, digitalisation of education